Analysis of contexts of coping with occupational stress: subjective experiences of educational support and social welfare professionals - Alifanovienė, Daiva; Gerulaitis, Darius; Kepalaitė, Albina; Šapelytė, Odeta; Vaitkevičienė, Asta (Social Welfare: Interdisciplinary Approach, 2019)
In the present article the impact of stress experienced by educational support and social welfare professionals on their professional activity and the opportunities of coping with it have been analysed applying a qualitative research approach. To analyse the subjective experience of educational support and social welfare professionals (N=27), a qualitative research approach has been chosen, the ontological basis of which consisted of the interpretive constructivist paradigm. The results of the research were validated using the expertise method: for external expertise the experts who did not participate in the research were employed, for internal expertise – persons who participated in the research and the researchers themselves. The data presented in the article are related both to the negative impact of stress on the professional activity and the positive impact leading to changes and improvement.
Keywords: occupational stress; the coping; educational support and social welfare professionals; subjective experience